The Significance of Upper Extremity Neuromonitoring Changes During Thoracolumbar Spine Surgery. Issue 8 (October 2018) - Atesok, Kivanc; Smith, Walter; Jones, Ross; Niemeier, Thomas; Manoharan, Sakthivel R.R.; McGwin, Gerald; Pittman, Jason; Theiss, Steven
Abstract : Study Design: This is a retrospective matched-pair cohort study. Objective: To investigate the significance of upper extremity (UE) neuromonitoring changes in patients undergoing thoracolumbar surgery in prone position. Summary of Background Data: Peripheral nerve injuries in the UEs due to the prone positioning during prolonged thoracolumbar spinal procedures can cause diminished postsurgical outcomes. Intraoperative neuromonitoring has been utilized to alert the surgeon of the development of such injuries. Materials and Methods: Patients who developed intraoperative ulnar somatosensory-evoked potential (SSEP) signal changes during posterior thoracolumbar surgery were identified and compared with a group of patients who did not develop such signal changes. The patients in 2 groups were pair-matched on the number of vertebral levels undergoing surgery. Data regarding intraoperative attempts to resolve signal changes and outcomes were collected. Results: In total, 843 patients underwent thoracic, lumbar, or thoracolumbar spine surgeries in the prone position with intraoperative ulnar SSEPs neuromonitoring data available. Of these, 37 patients (4.4%) had intraoperative signal changes in the UEs. An equal number of patients without signal changes were also selected. In each group, 6 patients underwent thoracic, 20 patients underwent lumbar, and 11 patients underwent thoracolumbar procedures. In 8 patients (21.6%), there was no resolution of SSEP signal changes despite intraoperative attempts. The 2 groups were similar with respect to age and comorbidities. There was no significant difference in the mean body mass index ( P =0.22). The mean duration of the procedures was 324 minutes in the SSEP signal change patients and 260 minutes in the patients without SSEP signal changes ( P =0.03). No patient with UE SSEP changes had a clinically detectable neurological deficit postoperatively. Conclusions: UE SSEP signal changes during multilevel posterior thoracolumbar procedures are more likely to occur as the duration of the operation increases. The presence of UE signal changes does not coincide with clinically significant peripheral neuropathies. Level of Evidence: Level III.